Geologic characteristics of deep water deposits and exploration discoveries in slope zones of fault lake basin: A case study of Paleogene Shahejie Formation in Banqiao-Qibei slope, Qikou sag, Bohai Bay Basin - Xianzheng ZHAO; Xiugang PU; Lihong ZHOU; Zhannan SHI; Wenzhong HAN; Wei ZHANG (Petroleum Exploration and Development, 2017)
Based on seismic, logging, formation testing, core and lab test data, this study analyzed the sequence division, facies features of deep water deposits and modes, development of large-scale gravity flow, reservoir physical properties and their main controlling factors, and proposed a classification standard and prediction method of favorable exploration areas in deep water area of the Bin1 oil layers of the lower sub-member of the first member of Paleogene Shahejie Formation in Banqiao-Qibei slope zone of Qikou sag, Bohai Bay Basin. The Bin1 oil layers can be divided into three fifth-order sequences, each less than 100 m thick; a set of gravity flow deposits were formed under deep water background in the slope zone, which contains sedimentary micro-facies such as main channel, distributary channel, channel margin, inter-channel mudstone, and turbidite sand sheet in areas without channels, and, in space, has inherited and constructive development features of multistages. It is a sedimentary sequence of fan delta – distal subaqueous fan – deep lake, and every distal subaqueous fan formed by gravity flow can be divided into inner-, middle- and outer fans. The cross-facies transported sands which are sourced from higher-sand-content major sands of delta front can form high quality reservoirs with an average porosity of 15.1% and geometric average permeability of 5.1×10−3 μm2. The main channel and distributary channel of distal subaqueous fan are the most favorable exploration zones. Key words: deep water deposit, slope zone, sandy debris flow, subaqueous fan, lithologic reservoir, Shahejie Formation, fault lake basin, Qikou sag, Bohai Bay Basin